THE USE OF TALKING CHIPS TECHNIQUE TO IMPROVE STUDENTSâ€™ SPEAKING SKILL - Fitriyanti, Anita; Rufinus, Albert; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to analyze the use of Talking Chips technique to improve studentsâ€™ speaking skill to eleventh grade students of SMA Kristen Makedonia Ngabang in Academic Year 2015/2016. This research was one of pre-experimental design, namely one group pre-test and post-test design. The sample was eleventh grade students ClassXI IPA 1, which consisted of 20 students. The tool used for collecting the data was pre-test and post-test. The test was reading aloud test. The research finding indicates that the studentsâ€™ mean score in post-test is 80 higher than their mean score in pre-test which is 63. It is found out that the result of the t-test is 7.79. The t-table with the degree of freedom 19 is 2.093. Because the result of t-test is higher than t-table, the alternative hypothesis â€œThe use of talking chips technique can improve studentsâ€™ speaking skill to the eleventh grade students of SMA Kristen Makedonia Ngabang in Academic Year 2015/2016â€ is accepted.Keywords: Talking Chips, Improve, Speaking skill